PENGARUH PUPUK HAYATI DAN PUPUK KCL TERHADAP PERTUMBUHAN DAN HASIL TANAMAN LOBAK (Raphanus sativus L.) PADA TANAH ALUVIAL - Lara, Lara Fitriyanti; Basuni, Basuni; Asri Mulya Ashari (Jurnal Pertanian Agros, 2025)
White radish (Raphanus sativus L.) is a vegetable plant in the form of a tuber. Radish for human health can especially smooth the digestive system. The purpose of this study was to determine the interaction between biofertilizer and KCl fertilizer on the growth and yield of radish plants on alluvial soil. This study was conducted in the Experimental Field of the Faculty of Agriculture, Tanjungpura University from March to April 2024. The method used was a Factorial Completely Randomized Design with two factors, the first factor was biofertilizer with 3 levels, and the second factor was KCL with 3 levels which were repeated 3 times so that there were 27 experimental units. The data obtained were analyzed statistically with the F test at a level of 5%. If the results of the F test show a significant effect, it is continued with the Honestly Significant Difference (HSD) test at a level of 5%. The variables observed in this study were the number of leaves (strands), leaf area (cm2), dry weight of plants (g), tuber length (cm), tuber diameter (cm), and fresh weight of tubers (g). The results of the study showed that the provision of 6 ml/l of water and 4.2 g of KCl fertilizer per polybag was the best treatment for the growth and yield of radish plants on alluvial soil.